Study review on nominal characteristic trajectory following controller for point-to-point positioning systems - Yakub, Mohd Fitri Mohd; Akmeliawati, Rini (2012)
This paper introduces study review on nominal characteristic trajectory following (NCTF) controller as a practical controller for point-to-point (PTP) positioning systems. PTP is one type of precision positioning systems that required high accuracy with a high speed, fast response with no or small overshoot and robustness to parameter variations and uncertainties. In PTP applications, parameter varies with the payload and some friction may cause the instability of the performances. In this case, the system performance is expected to be the same or as close as its performance when the system is in normal condition. PTP positioning systems need a good controller to achieve high speed and high precision motion. However, it is not easy to achieve high precision system because of nonlinearities and uncertainties exist in the motion control systems. A NCTF controller as a practical controller for PTP had been proposed. The NCTF controller consists of two elements namely a nominal characteristic trajectory (NCT) and a compensator. It had been reported that the NCTF had a good positioning performance and robustness to parameters variations. Application of NCTF control for PTP positioning systems both for one-mass system or multi-mass system are studied and summarized. Fundamental concept of NCTF controller also explained.